El principio de coordinación del contrato de prestación de servicios regulado en la Ley 80/1993 (2020)
Provision of services agreements are inside of the contractual typology compiled in the law 80 from 1993. Those are consecrated as a cause of direct contract inside of literal h, article 02 of the Law 1150 from 2007. Those contracts have been celebrated by the state entities being analyzed in many occasions. In this case, this article will focus on the reality primacy principle over the formalities facing to the activities’ execution coordination principle. Therefore, it takes on a higher relevance by the paradigm change of the Council State from a progressive position, in which it argues, even though, it is not possible to infringe it to the contractor, constitutional principles like those on the article 53 of the Political Constitution of 1991. . Besides, it is true that the contractor must carry out the activities for the entity in the frame of the entity mission and duties related to the Constitution or the law.